Guidelines for accurate and transparent health estimates reporting: the GATHER statement - Stevens, G; Alkema, L; Black, R; Boerma, J; Collins, G; Ezzati, M; Grove, J; Hogan, D; Hogan, M; Horton, R; Lawn, J; Marušić, A; et al. (Public Library of Science, 2016)
Gretchen Stevens and colleagues present the GATHER statement, which seeks to promote good practice in the reporting of global health estimates.